2018
DOI: 10.1002/mc.22531
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability of formononetin to stimulate proliferation of endothelial cells and breast cancer cells via a feedback loop involving MicroRNA‐375, RASD1, and ERα

Abstract: For postmenopausal cardiovascular disease, long-term estrogen therapy may increase the risk of breast cancer. To reduce this risk, estrogen may be replaced with the phytoestrogen formononetin, but how formononetin acts on vascular endothelial cells (ECs) and breast cancer cells is unclear. Here, we show that low concentrations of formononetin induced proliferation and inhibited apoptosis more strongly in cultured human umbilical vein endothelial cells (HUVECs) than in breast cancer cells expressing estrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In addition, astragaloside isoflavanthin can regulate the immune system and enhance the body's function of producing interferon ( Yang et al, 2014 ). Formononetin has pharmacological effects such as lowering blood pressure, regulating inflammatory responses and lipid metabolism ( Chen et al, 2018 ). Attractylone may inhibit apoptosis by regulating PI3K-AKT pathway and other mechanisms ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astragaloside isoflavanthin can regulate the immune system and enhance the body's function of producing interferon ( Yang et al, 2014 ). Formononetin has pharmacological effects such as lowering blood pressure, regulating inflammatory responses and lipid metabolism ( Chen et al, 2018 ). Attractylone may inhibit apoptosis by regulating PI3K-AKT pathway and other mechanisms ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies showing formononetin antiproliferative potential against different cancer cell lines [21], emphasizing its selective activity against ER-positive breast cancer cells, i.e., MCF-7, and the lack of effectiveness in the case of ER-negative MDA-MB-231 cells [22]. In spite of this, Chen et al demonstrated its proliferation inhibition and apoptosis induction in MCF-7 and MDA-MB-231 cells, with, however, lower efficiency against HUVECs [23]. Authors suggested that observed cellular selectivity was connected with presence of a feedback loop involving miR-375, ras dexamethasone-induced 1 (RASD1) and ERα in HUVECs, but not in MCF-7 cells.…”
Section: Assessment Of Trifolium Pratense L Extracts On Cellular Viamentioning
confidence: 99%
“…RASD1 belonged to the Ras family is originally regarded as a dexamethasone-inducible gene, and its product is a receptor-independent activator of G-protein signal 33 , 34 . Although there are still some controversies regarding the roles RASD1 played in carcinogenesis, many studies revealed that RASD1 could serve as a tumor suppressor in diverse malignancies 35 38 .…”
Section: Discussionmentioning
confidence: 99%